PERANAN DPRD DALAM PEMBENTUKAN PERATURAN DAERAH PROVINSI KALIMANTAN TIMUR - Nanik Pujiastuti dan Joko Setia Budi (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2019)
The purpose of this research is to find out how the role of the DPRD inthe formation of regional regulations in East Kalimantan Province. Theresults of the study show that in general the role of the DPRD is manifested inthree functions as stated in Law Number 23 Year 2014, namely the formationof regional regulations, budgets and supervision. In connection with this, theformation of regional regulations is the main function of the DPRD. Incarrying out this function, especially in terms of initiatives or initiatives tomake regional regulations by the DPRD of East Kalimantan Province it can besaid that it has already been implemented. This can be seen from the initiativeof making regional regulations not only from the provincial government butalso from the DPRD initiative and this certainly has been in line with themandate of Law Number 12 Year 2011 article 56 which states that "The draftprovincial regulations can come from the DPRD Provincial or Governor"andGovernment Ordinance Number 12 Year 2018 article 5 section (1) whichstates that"Draft regional regulations can come from DPRD or RegionalHead".